Phenolic Compound Production Increased In Vitro Regenerated Cichorium intybus L. - Abas, Yousif Abdullah; Eroglu, Ayten; Dalar, Abdullah; Turker, Musa; Ozdemir, Fethi Ahmet; Solowski, Gawel (MDPI, 2023)
Chicory (Cichorium intybus L.) is a low-height perennial or biennial herb from the family of Asteraceae. Investigation of different in vitro regeneration strategies of Cichorium intybus and increasing the number of secondary metabolites in vitro regenerated plant samples were the aims of the research. Callus and plant regenerations were achieved in basal plant growth media supplemented with plant growth regulators (PGRs). Whole plant regeneration was carried out by direct organogenesis from leaf explant in Murashige and Skoog (MS) and B5 media supplemented with naphthalene acetic (NAA) acid and indole-3-butyric acid (IBA). The highest callus quantity was produced in MS medium supplemented with indole-3-acetic acid (IAA) and benzyl amino purine (BAP). The combination and concentrations of PGRs used in MS and B5 media not only provided root and shoot formation with callus, but also caused a change in the amounts of phenolic components. In addition, some PGRs used caused an increase in the number of phenolic compounds in callus and shoots developed from the leaf explant. When plants that grow in vitro and in vivo are compared with each other, it has been determined that plants grown in vivo contain higher amounts of some phenolic compounds. In vivo and in vitro samples were extracted in ethanol/water (80:20 v/v). The analysis of phenolic compounds (caftaric, chicoric, and chlorogenic acids and esculin) were performed in high-performance liquid chromatography (HPLC) and inulin was in UV spectrophotometry. The caftaric and chlorogenic acids and inulin concentrations were higher in vivo samples than that in vitro. Contrarily, esculin, and chicoric acid concentrations were higher in the in vitro regenerated samples. The higher concentration of valuable compounds in the in vitro regenerated samples, especially in callus tissue, gives hope for large-scale production of secondary metabolites under laboratory conditions.
Keywords: Cichorium intybus L.; in vitro; phenolic compounds; inulin; ACID; MICROPROPAGATION; ANTIOXIDANT; Biotechnology & Applied Microbiology